Hybrid Aortic Arch Repairs - Morishita, Kiyofumi (Ann Vasc Dis, 2019)
Hybrid aortic arch repair (HAAR) consists of thoracic stent-graft repair and procedures to maintain cerebral blood flow. Several hybrid techniques have been used, including arch artery debranching, parallel graft technique, fenestration or branching of endograft, or a combination of these. We provided an overview of HAAR by presenting literature reviews as well as our clinical experience. The experience consisted of 172 patients who had undergone HAAR. The 30-day mortality was 3% (5/172). Persistent neurologic deficits occurred in 7 patients (4%), respiratory failure in 5 (3%), de novo aortic dissection in 3 and spinal cord injury in 2. 17% of the patients experienced type Ia endoleak. Seventeen patients required redo thoracic endovascular aortic repair. Fifty-six late deaths occurred during the follow-up period, including aortic-related death in 9 patients. In conclusion, hybrid arch debranching repair should be performed for elderly or high-surgical-risk patients. However, refining techniques and device technology is likely to reduce late endograft-related events. (This is a translation of Jpn J Vasc Surg 2018; 27: 385–391.)